ANALYSIS OF CEMENT AS RAW MATERIAL INVENTORY ON READY MIX PRODUCTION UNIT AT PT. PERDANA BETON IN SAMARINDA - Wahyuni, Novita Eka (EKONOMIA, 2014)
This study aims to identify and analyze the optimal amount of cement supplies in PT. Perdana Beton In Samarinda.            Formulation of the problem in this study is whether the supply of cement as raw material for Ready Mix at PT. Perdana Beton In Samarinda already minimizing the cost of inventory cement.            The hypothesis in this study is: '' Allegedly cement as raw material supplies ready mix at PT. Perdana Beton In Samarinda not provide minimum inventory costs'.            Basic theory used in this study are: Operations Management Definition of Management consisting of, Understanding Operations Management, Management Philosophy, Definition of Production Management, Operations and Functions, Definition of Operations Management, Operations Management Functions, and Inventory Management.Analysis tools are used is particularly operational management of inventory theory using data in 2013, supplies of cement calculated using the Model Economic Order Quantity (EOQ) as an analytical tool. Economic Order Quantity (EOQ) is a model concerning the provision or supply of raw materials at a company. Each company must require industry raw materials for smooth business processes, the raw materials obtained from a supplier with a particular calculation. By using economic calculation can determine the course of a company on a regular basis how and how much material must be provided. Scheduling irregularity will have an impact on inventory costs by stacking in warehouse inventory. Thus, management or arrangement of raw materials is one of the important things and can save the company money.            Thus, the hypothesis put forward previously stating that the supply of cement as raw material ready mix in PT. Perdana Beton In Samarinda not provide acceptable minimum inventory costs.